Bullous cutaneous larva migrans: an atypical case of creeping eruption - Salvatierra, Lidianne (Saúde (Santa Maria), 2021)
Cutaneous larva migrans is a hookworm-related infestation caused by zoonotic nematode larvae such as the Ancylostoma braziliense. Herein a case of a 2-year-old child complaining initially of painfull blisters on her left foot is report. The correct diagnosis was delayed and only confirmed when serpiginous, erythematous tracks and bullae were developed. Patient was treated with fexofenadine oral, topical thiabendazole and a cream with ketoconazole, betamethasone dipropionate and neomycin sulfate. The reported case assumes importance because of the atypical presentation of the disease as a case of bullous cutaneous larva migrans.